Limits to Dihydrogen Incorporation into Electron Sinks Alternative to Methanogenesis in Ruminal Fermentation - Ungerfeld, Emilio M. (Frontiers in Microbiology, 2015)
Research is being conducted with the objective of decreasing methane (CH4) production in the rumen, as methane emissions from ruminants are environmentally damaging and a loss of digestible energy to ruminants. Inhibiting ruminal methanogenesis generally results in accumulation of dihydrogen (H2), which is energetically inefficient and can inhibit fermentation. It would be nutritionally beneficial to incorporate accumulated H2 into propionate or butyrate production, or reductive acetogenesis. The objective of this analysis was to examine three possible physicochemical limitations to the incorporation of accumulated H2 into propionate and butyrate production, and reductive acetogenesis, in methanogenesis-inhibited ruminal batch and continuous cultures: i) Thermodynamics; ii) Enzyme kinetics; iii) Substrate kinetics. Batch (N = 109) and continuous (N = 43) culture databases of experiments with at least 50% inhibition in CH4 production were used in this meta-analysis. Incorporation of accumulated H2 into propionate production and reductive acetogenesis seemed to be thermodynamically feasible but quite close to equilibrium, whereas this was less clear for butyrate. With regard to enzyme kinetics, it was speculated that hydrogenases of ruminal microorganisms may have evolved towards high-affinity and low maximal velocity to compete for traces of H2, rather than for high pressure accumulated H2. Responses so far obtained to the addition of propionate production intermediates do not allow distinguishing between thermodynamic and substrate kinetics control.